HMGB1 Activates Myeloid Dendritic Cells by Up-Regulating mTOR Pathway in Systemic Lupus Erythematosus - Song, Xinghui; Zhang, Hui; Zhao, Yun; Lin, Yuanzhen; Tang, Qiya; Zhou, Xiu; Zhong, Xiaoning (Frontiers in Medicine, 2021)
It is manifested that HMGB1 can activate dendritic cells (DCs), but its molecular mechanisms are not yet clear. In this study, we report that the mDCs were activated in SLE's peripheral blood, and the mDCs' activation was associated with up-regulation HMGB1 and mTOR. After HMGB1 stimulus, mTOR expression and its substrates P70S6K and 4EBP1 in dendritic cells increased considerably (P<0.01). The expression of HLA-DR, CD40, and CD86 on dendritic cells also significantly increased following these stimuli (P<0.01). Besides, stimulation with HMGB1 led to enhancing cytokine (IL-1β, IL-6, and TNF-a) production in dendritic cells. In contrast, the HMGB1-mediated expression of HLA-DR, CD40, and CD86 on dendritic cells, and production of IL-1β, IL-6, and TNF-a were reduced by rapamycin. Rapamycin can inhibit HMGB1-induced activation of mDCs and secretion of pro-inflammatory cytokines. These findings indicate that HMGB1activates DCs by up-regulating the mTOR pathway in SLE.